The Impact of Endometriosis on Embryo Quality in in-vitro Fertilization/Intracytoplasmic Sperm Injection: A Systematic Review and Meta-Analysis - Dongye, Houjin; Ji, Xiaofeng; Ma, Xiaopei; Song, Jialun; Yan, Lei (Frontiers in Medicine, 2021)
Background: The association between endometriosis and embryological outcomes remains uncertain. The meta-analysis aimed to evaluate the impact of endometriosis on embryo quality. Methods: A systematic review and meta-analysis was conducted to investigate the association between the endometriosis and embryo quality. Searches were performed on the three electronic databases: PubMed, EMBASE and Web of Science. The detailed characteristics and data of the included studies were extracted. The risk ratio with 95% confidence intervals were calculated using the random and fixed effects model. The main outcome measures were high-quality embryo rate, cleavage rate and embryo formation rate. Results: A total of 22 studies included were analyzed. Compared with the control group, women with endometriosis had a similar high-quality embryo rate (RR=1.00; 95% CI, 0.94-1.06), a comparable cleavage rate (RR=1.00; 95% CI, 0.97-1.02) and a similar embryo formation rate (RR=1.10; 95% CI, 0.97-1.24). In women with stage Ⅲ-Ⅳ endometriosis, there was no statistically significantly difference in high-quality embryo rate (RR=1.02; 95% CI, 0.94-1.10), cleavage rate (RR=1.00; 95% CI, 0.98-1.02) and embryo formation rate (RR=1.05; 95% CI, 0.97-1.14), compared with those without endometriosis. For women with unilateral endometriosis, pooling of results from the affected ovaries did not show a statistically significantly difference in high-quality embryo rate (RR=0.99; 95% CI, 0.60-1.63) in comparison to the normal contralateral ovaries. Conclusions: Our results seem to indicate that endometriosis does not compromise embryo quality from the perspective of morphology.